Investigation of Adsorption of 5-Bromouracil from Aqueous Solutions to Montmorillonite and Its Interaction with Clay Framework: A FT-IR Spectroscopic Study - Akyuz, T.; Akyuz, S. (Asian Journal of Chemistry, 2011)
Adsorption of 5-bromouracil molecules onto montmorillonite was studied by FT-IR spectrometry. 5-Bromouracil, a thymine antagonist, is used to treat inflammatory tissues. The intercalation of 5-bromouracil within montmorillonite has been shown by X-ray diffraction to increase the interlayer spacing. The results indicate that sorbed 5-bromouracil molecules on montmorillonite are coordinated to exchangeable cations indirectly through water bridges.